Loading calcium fluorescent probes into protoplasts to detect calcium in the flesh tissue cells of Malus domestica. (1st June 2020) - Qiu, Lina; Wang, Yongzhang; Qu, Haiyong
Abstract: Cytosolic Ca 2+ plays a key role in signal transduction in plants. Calcium imaging is the most common approach to studying dynamic changes in the cytoplasmic Ca 2+ content. Here, we used mature 'Fuji' apples ( Malus pumila Mill .) to obtain viable protoplasts from flesh tissue cells by enzymatic hydrolysis; then, three small-molecule fluorescent probes (fluo-8/AM, fluo-4/AM, and rhod-2/AM) were loaded into the protoplasts. All three Ca 2+ fluorescent probes successfully entered the cytoplasm but did not enter the vacuole. Both the Ca 2+ chelator (EGTA) and Ca 2+ channel blocker (La 3+ ) reduced the fluorescence intensity in the cytoplasm. The calcium ionophore A23187 increased the fluorescence intensity in the cytoplasm at 5 µmol/L but decreased it at 50 µmol/L. Additionally, A23187 reversed the fluorescence intensity in the cytoplasm, which was decreased by La 3+ . Ionomycin is also a calcium ionophore that can increase the fluorescence intensity of calcium in the cytoplasm. These results suggest that small-molecule Ca 2+ fluorescent probes can be used to detect changes in cytosolic calcium levels in the cells of fruit flesh tissue. In addition, the optimum concentration of fluo-8/AM was determined to be 5 µmol/L. This was the first time that protoplasts have been isolated from apple flesh tissue cells and small-molecule fluorescent probes have been used to detect calcium in the cytoplasm of flesh tissue cells. This study provides a new method to study calcium signal transduction in fruit flesh tissue.